CORONARY ARTERY PATHOLOGY IN RIGHT VENTRICULAR MYOCARDIAL INFARCTION - G. G. Ayrapetyan; K. G. Adamyan (Кардиоваскулярная терапия и профилактика, 2013)
Aim. To study anatomical and functional features of coronary blood flow in myocardial infarction (MI) of left ventricular (LV) inferior wall with the involvement of right ventriculum (RV).Material and methods. The study included 120 patients who suffered MI of LV inferior wall with (Group 2 – LVMI; n=58) or without (Group 1 – RVMI; n=62) RV involvement.Results. One coronary artery (CA) was affected in 65,0% of the participants. Right CA (RCA) pathology was registered in 97,4% (n=76), while circumflex CA (CxCA) pathology was observed only in 2,6% (n=2). Involvement of two and three or more CA was observed in 26,7% and 8,3% of the patients, respectively. Single CA pathology was at least 1,3 times more common in the RVMI group (p<0,05), while three or more CA were affected at least 8 times more often in the LVMI group (p<0,05). The right dominant, co-dominant, and left dominant types of coronary flow were registered in 76,7%, 15,0%, and 8,3% of the patients, respectively, all of whom were from the LVMI group. In 85% and 15% of the cases, the infarct-related artery (IRA) was RCA and CxCA, respectively. Among LVMI patients, RCA was the IRA almost three times more often than CxCA; among RVMI patients, this difference was 18-fold (p<0,001 for both comparisons). All LVMI patients (n=47) had distal occlusion of RCA, while all RVMI patients (n=55) had its proximal occlusion.Conclusion. Over two-thirds of the cases оf ST elevation MI of LV inferior wall with RV involvement occur in patients with the right dominant type of coronary blood flow. RVMI typically occurs in patients with right dominant type of coronary blood flow and PCA pathology. MI of LV inferior wall with RV involvement is characterised by proximal RCA occlusion.